MAKING SINGLE COMPLETE DENTURES FOR THE MATERIAL WITH TUBER MAXILLA CASE LARGE - Kusdarjanti, Endang; Setyowati, Okti; Zseni, Febriana (Journal of Vocational Health Studies, 2019)
Background: Single complete denture is complete denture where its antagonist there tooth original good in part or else entirely. Besides that on case this there bulge tuber maxilla more big of the normal size of course only will complicate at the stage of preparation of teeth and also take effect on retention, stability, and comfort. Purpose: To discuss about technique manufacture single complete denture with a large tuber maxilla. Review: Single complete denture is a complete denture in which the antagonistic teeth can be either partial or whole natural teeth. Whereas complete denture is a complete maxillary and mandibular denture that is used if both jaws do not have natural teeth. To get good inclination and occlusal surface can do with Swenson technique and Yurkstas technique which is use a compensating curve template to determine the occlusal views of Wilson's curve and spee curve. Conclusion: in the making single complete denture, moment preparation tooth there difficulty because have a big maxilla and need a lot of grinding on dental elements and additions anasir second premolar teeth for get aesthetic and functional is good, too take effect to retention and stability.